Environmental sustainability assessment of poultry productions through life cycle approaches: A critical review. (April 2021) - Costantini, Michele; Ferrante, Valentina; Guarino, Marcella; Bacenetti, Jacopo
Abstract: Background: Poultry production is an important human food pillar and is experiencing continuous growth worldwide. The Life Cycle Assessment (LCA) approach has been increasingly used for providing information on poultry production chains, in particular from the environmental point of view, which has also been coupled with economic or social considerations in some cases. Scope and approach: This study aimed to undertake a critical review to the state of the art of LCA application to the poultry sector. Attention has been drawn to the different methodological approaches adopted in the literature regarding functional units, system boundaries, inventory data collection and multifunctionality management. In addition to reviewing how this sector was methodologically approached by means of the LCA, this study aimed to summarize the main findings and highlight current shortcomings of the literature. Key findings and conclusions: Chicken chains were by far the most analyzed. A multiplicity of approaches was implemented to date for the evaluation of these products in a life cycle perspective but the most adopted ones were the mass based functional unit, the cradle-to-farm gate perspective and the economic allocation. As for other animal products, the agricultural phase weighs heavily on the impact of the finished food product, in particular due to feed consumption and manure management. The discussion focuses on the parameters most influencing environmental performance, as well as on possible mitigations, some already widely known while others still partially unexpressed. Finally, some research topics are identified that could increase the understanding and consequently the sustainability of this important supply chain in the future. Highlights: The review focuses on the environmental impact of poultry productions. 155 studies were identified, 47 reviewed in detail. Functional unit, system boundary and multifunctionality management were identified. The agricultural phase weighs heavily on the impact of the finished food product. Feed consumption and manure management are the main impact contributors.